Viscoelastic evaluation of epoxy nanocomposite based on carbon nanofiber obtained from electrospinning processing - de Oliveira, Juliana Bovi [UNESP] (2019)
In recent years, carbon nanofiber composites have attracted researchers worldwide to use in reinforcing nanofillers instead of traditional methods due mainly to their multifunctional properties. Carbon nanofibers promote good thermal conductivity, high surface area, high chemical stability and good mechanical resistance when associated with epoxy resin, for example, being excellent candidates for the acquisition of advanced composites. The production of blankets made of interconnected fibers with diameters of micrometers and nanometers can be obtained by the electrospinning process using a polymer solution. This work has as main objective the production of carbon nanofibers, using as precursor the polyacrylonitrile (PAN) blanket obtained by the electrospinning process through polymer solution and subsequent carbonization aiming applications as reinforcement in polymer composites. The fibers obtained by the electrospinning technique and subsequently passed through the carbonization process were characterized by scanning electron microscopy (SEM), which showed a decrease in the size of the fibers after carbonization, and by Fourier transform infrared spectroscopy, where a chemical change in the structure of the PAN was observed after its carbonization. The nanocomposite of epoxy resin/carbon nanofibers was characterized by dynamic mechanical analyses and thermomechanical analyses. The epoxy resin/carbon nanofiber composite presented a glass transition temperature (Tg) in the range from 108.9 to 135.5 °C and a linear thermal expansion coefficient within the range of 68 × 10 −6 /°C and 408 × 10 −6 /°C.